A tubular one‐dimensional polymer constructed from alternating clusters of europium(III)–water and copper(I) chloride bridged by 4‐(pyridin‐4‐yl)benzoate. (12th June 2013) - Cao, Gao‐Juan; Li, Qing‐Lu; Rong, Cheng; Wang, Yu‐Lin
Abstract : A new 3 d –4 f heterometallic polymer, poly[[aqua‐μ3 ‐chlorido‐[μ3 ‐4‐(pyridin‐4‐yl)benzoato]tris[μ2 ‐4‐(pyridin‐4‐yl)benzoato]dicopper(I)erbium(III)] dihydrate], [Cu2 Er(C12 H8 NO2 )4 Cl(H2 O)]·2H2 O n, was synthesized by the hydrothermal reaction of Er2 O3, CuCl2 ·2H2 O and 4‐(pyridin‐4‐yl)benzoic acid in the presence of HClO4 . The asymmetric unit contains one Er 3+ cation, two Cu + cations, one Cl − anion, four deprotonated 4‐(pyridin‐4‐yl)benzoate ligands, one coordinated aqua ligand and two solvent water molecules. This tubular one‐dimensional polymer is constructed from alternating clusters of europium(III)–water and copper(I) chloride bridged by 4‐(pyridin‐4‐yl)benzoate ligands. Extensive hydrogen‐bonding interactions involving both the coordinated and the solvent water molecules provide further stabilization to the structure.